Analisis Penyuntingan Kalimat Efektif pada Naskah Novel “Berjuta Rasanya” Karya “Tere Liye” - Dewi Insyiroh; Inayah Alfina Wulandari; Shafa Aura Anindya; Mohamad Afrizal (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2026)
This study aims to analyze the application of effective sentences in the novel Berjuta Rasanya by Tere Liye and to examine relevant aspects of manuscript editing. An effective sentence is one that conveys ideas precisely, clearly, and without ambiguity. In literary works, the use of effective sentences plays a crucial role in maintaining readability and the aesthetic quality of the language. This research employs a qualitative descriptive method using content analysis techniques. The data are drawn from sentences in the novel that reflect the characteristics of balance, economy, parallelism, logic, variation, and emphasis. The results indicate that the novel contains both effective sentences and sentences requiring editing, particularly in terms of economy and parallelism. The editing process was carried out in accordance with Indonesian grammar rules while preserving the author's distinctive style. The implications of this research may serve as a reference for literary manuscript editing and text-based Indonesian language learning.